2010
DOI: 10.1002/ijc.25023
|View full text |Cite
|
Sign up to set email alerts
|

No role for human papillomavirus in esophageal squamous cell carcinoma in China

Abstract: Certain regions of China have high rates of esophageal squamous cell carcinoma (ESCC). Previous studies of human papillomavirus (HPV), a proposed causal factor, have produced highly variable results. We attempted to evaluate HPV and ESCC more definitively using extreme care to prevent DNA contamination. We collected tissue and serum in China from 272 histopathologically-confirmed ESCC cases with rigorous attention to good molecular biology technique. We tested for HPV DNA in fresh-frozen tumor tissue using PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 49 publications
3
71
0
Order By: Relevance
“…Furthermore, eight studies were excluded because of the limited number. In total, we included 26 eligible studies in the meta-analysis (Cao et al, 2005;Yang et al, 2005;Dai et al, 2007;He et al, 2007;Shuyama et al, 2007;Zhou et al, 2007;Chen et al, 2008;Li et al, 2008;Liu et al, 2008;Lu et al, 2008;Zhao et al, 2009;Liu et al, 2010;Koshiol et al, 2010;Wang et al, 2010;Ayshamgul et al, 2011;Han et al, 2011;Zhang et al, 2011;Guo et al, 2012;Hu et al, 2012;Qu et al, 2012;Liu et al, 2013;Zhang et al, 2013;Cui et al, 2014;Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, eight studies were excluded because of the limited number. In total, we included 26 eligible studies in the meta-analysis (Cao et al, 2005;Yang et al, 2005;Dai et al, 2007;He et al, 2007;Shuyama et al, 2007;Zhou et al, 2007;Chen et al, 2008;Li et al, 2008;Liu et al, 2008;Lu et al, 2008;Zhao et al, 2009;Liu et al, 2010;Koshiol et al, 2010;Wang et al, 2010;Ayshamgul et al, 2011;Han et al, 2011;Zhang et al, 2011;Guo et al, 2012;Hu et al, 2012;Qu et al, 2012;Liu et al, 2013;Zhang et al, 2013;Cui et al, 2014;Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, judgment-based merely on the overall exposure to ABC was insufficient because the false-positive rate (55%) was high. Both of the infectious pathogens H. pylori and human papillomavirus were not associated with SCC risk (37,38). Although several risk alleles have been previously identified (10-13), they served as effect modifiers rather than direct causes.…”
Section: Discussionmentioning
confidence: 97%
“…However, the presence of HPV DNA in esophageal carcinomas has been a highly controversial issue (16,20,22,32). Differences in sampling methods, demographic and ethnic factors, disease status, and sensitivity of detection methods have been suggested to be potential causes of the discrepancies in findings (16).…”
Section: Discussionmentioning
confidence: 99%
“…We have frequently detected HPV DNA in esophageal squamous cell carcinoma (ESCC) tissues collected from patients in Anyang (19), a high-incidence area for ESCC in China, whereas other studies failed to produce comparable results in samples collected from same region and concluded there was no association between HPV infection and ESCC (20)(21)(22). Our previous study (refer to the Supplementary data) and a study from other investigators have observed that HPV viral load in ESCC is much lower than in cervical cancer tissues (23).…”
Section: Introductionmentioning
confidence: 91%